2020
DOI: 10.3748/wjg.v26.i44.7061
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum uric acid and hepatobiliary-pancreatic cancer: A cohort study

Abstract: BACKGROUND Uric acid is the end product of purine metabolism. Previous studies have found that serum uric acid (SUA) levels are associated with the total cancer risk. However, due to the dual effect of uric acid on cancer, the relationship between the SUA levels and most specific-site cancer remains unclear. AIM To investigate the associations between the SUA levels and incidence of hepatobiliary-pancreatic cancer. METHODS In this prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
1
11
0
1
Order By: Relevance
“…Uric acid has been found being a prooxidant, and contributes to tumorigenesis via reactive oxygen species and inflammatory stress [ 95 , 96 ]. Previous studies have shown that uric acid induces hepatocyte fat accumulation [ 97 ], development of non-alcoholic fatty liver disease (NAFLD) [ 97 , 98 , 99 , 100 , 101 ], liver cirrhosis [ 102 , 103 ] and hepatocellular carcinoma [ 96 , 104 ]. In this study, we found that miR-143 loss inhibited purine synthesis in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid has been found being a prooxidant, and contributes to tumorigenesis via reactive oxygen species and inflammatory stress [ 95 , 96 ]. Previous studies have shown that uric acid induces hepatocyte fat accumulation [ 97 ], development of non-alcoholic fatty liver disease (NAFLD) [ 97 , 98 , 99 , 100 , 101 ], liver cirrhosis [ 102 , 103 ] and hepatocellular carcinoma [ 96 , 104 ]. In this study, we found that miR-143 loss inhibited purine synthesis in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid is the end product of the purine metabolism pathway, and is an antioxidant scavenging free radicals in the body (8,9). Recent evidences have linked serum uric acid (SUA) to cancer risks in adulthood (10,11). Studies show that hyperuricemia is associated with an increased cancer incidence and mortality (12), while some other conflicting reports have suggested a protective role of SUA in cancer due to its antioxidant properties (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…CD8+ T cells can inhibit cancer cell proliferation and migration and induce cytotoxic cell death, which may be one of the mechanisms of tumor protection 19 . Recently, several studies have focused on establishing the association between low SUA levels and cancer risk, supporting a U‐shaped association between SUA levels and cancer mortality 20‐22 …”
Section: Introductionmentioning
confidence: 99%
“…19 Recently, several studies have focused on establishing the association between low SUA levels and cancer risk, supporting a U-shaped association between SUA levels and cancer mortality. [20][21][22] Colorectal cancer, ranking second in cancer mortality, is also the second most frequently diagnosed cancer in females and ranks third in males, with 1.8 million new cases and 88 100 deaths in 2018. 23,24 Dziaman et al found that uric acid levels were significantly associated with the prognosis of colon cancer patients, and the life span of patients with high uric acid is longer than that of patients with low uric acid levels (lower than 277.8 μM).…”
Section: Introductionmentioning
confidence: 99%